Optimalisasi Layanan Guest Service Center Dalam Menciptakan Kepuasan Tamu (Studi Pada Gumaya Tower Hotel Semarang) - Setya, Azizah Dwi; Sulistyo, Agung; Christiatmani, MMA (Jurnal Manajemen DIVERSIFIKASI, 2024)
The presence of hotels as a tourism-supporting industry is expected to be able to meet tourist expectations. As the tourism sector develops, the hotel industry continues to grow. The large number of accommodation service providers means that hotel management faces business competition. Service instruments can be one of the considerations for used. The success of the hotel business is not only related to strategy but also to the communication carried out. Through the guest service centre division, it is hoped that it will support the achievement of sustainability and hotel guest satisfaction. This study uses a qualitative research design in an effort to uncover service practices carried out at the Gumaya Tower Hotel. To produce quality interview data, service instruments were used in this research. Some of these instruments include responsiveness, assurance, empathy, reliability, and tangible. Guest service centre staff were chosen as research informants. The Miles Huberman method was used to maintain the quality of the data produced. In an effort to maintain the validity of the data, triangulation techniques were used in this research. The Gumaya Tower Hotel staff has fully implemented the service concept, according to the analysis. This instrument is able to provide hotel guests with satisfaction. Furthermore, the findings of this research can be used as a guide to creating quality services.